Conformity to masculine norms, masculine discrepancy stress, and changes in muscle dysmorphia symptoms. (March 2022) - Grunewald, William; Kinkel-Ram, Shruti S.; Smith, April R.
Highlights: Few risk factors for Muscle Dysmorphia (MD) development have been identified. Longitudinal relationships between masculinity and MD symptoms were investigated. Specific masculine norms were bidirectionally related to MD symptoms over time. Masculine discrepancy stress did not mediate these relationships as hypothesized. Conformity to specific masculine norms may be a risk factor for MD development. Abstract: Muscle dysmorphia (MD) is a severe psychiatric illness; however, little is known regarding risk factors for MD development. Conformity to masculine norms may represent a risk factor for MD, but research has yet to establish temporal ordering for these relationships. Masculine discrepancy stress (distress at not amounting to masculine stereotypes) could represent a mechanism underlying these relationships. Therefore, the current study examined longitudinal relationships between conformity to masculine norms, masculine discrepancy stress, and MD symptoms. Participants were 272 men displaying elevated MD symptoms who completed self-report questionnaires at three timepoints. An autoregressive cross-lagged mediation model was specified to examine relationships between conformity to masculine norms and MD symptoms and test if masculine discrepancy stress mediated these relationships. Masculine discrepancy stress did not mediate relationships between masculine norms and MD symptoms. However, MD symptoms predicted increased masculine discrepancy stress, and conformity to masculine norms was related to MD symptoms. MD symptoms were both a predictor and outcome of masculine norms, and signs for relationships differed on the masculine norm endorsed. Conformity to masculine norms may represent a risk factor and outcome for MD symptoms. If clinicians provide clients with tools to reduce rigid adherence to masculine identities, this may prevent MD symptom development.